Essential roles of HDAC1 and 2 in lineage development and genome-wide DNA methylation during mouse preimplantation development. Issue 4 (2nd April 2020) - Zhao, Panpan; Wang, Huanan; Wang, Han; Dang, Yanna; Luo, Lei; Li, Shuang; Shi, Yan; Wang, Lefeng; Wang, Shaohua; Mager, Jesse; Zhang, Kun
ABSTRACT: Epigenetic modifications, including DNA methylation and histone modifications, are reprogrammed considerably following fertilization during mammalian early embryonic development. Incomplete epigenetic reprogramming is a major factor leading to poor developmental outcome in embryos generated by assisted reproductive technologies, such as somatic cell nuclear transfer. However, the role of histone modifications in preimplantation development is poorly understood. Here, we show that co-knockdown (cKD) of Hdac1 and 2 (but not individually) resulted in developmental failure during the morula to blastocyst transition. This outcome was also confirmed with the use of small-molecule HDAC1/2-specific inhibitor FK228. We observed reduced cell proliferation and increased incidence of apoptosis in cKD embryos, which were likely caused by increased acetylation of TRP53. Importantly, both RNA-seq and immunostaining analysis revealed a failure of lineage specification to generate trophectoderm and pluripotent cells. Among many gene expression changes, a substantial decrease of Cdx2 may be partly accounted for by the aberrant Hippo pathway occurring in cKD embryos. In addition, we observed an increase in global DNA methylation, consistent with increased DNA methyltransferases and UHRF1. Interestingly, deficiency of RBBP4 and 7 (both are core components of several HDAC1/2-containing epigenetic complexes) results in similar phenotypes as those of cKD embryos. Overall, HDAC1 and 2 play redundant functions required for lineage specification, cell viability and accurate global DNA methylation, each contributing to critical developmental programmes safeguarding a successful preimplantation development.